Surcharge dalam Transaksi QRIS : Analisis Perlindungan Konsumen dan Penegakan Hukum Berdasarkan Peraturan Bank Indonesia - Ratu Inaz Mumtakhinah; Salsabila Triandani; Nadine Azzahra Noor; Rizki Fitrianti Apriliani; Bulan Ichlasul Cahya Ramadhani; Baidhowi (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The advancement of information technology has significantly transformed payment systems from cash-based transactions to digital methods. In Indonesia, one of the prominent innovations is the Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia as a national standard for QR code-based payments. QRIS is designed to enhance transaction efficiency, promote financial inclusion, and support the expansion of the digital economy. However, in practice, some merchants still impose additional charges on consumers when using QRIS, either as a fixed fee or a percentage of the transaction amount. This practice contradicts Bank Indonesia Regulation Number 23/6/PBI/2021, which prohibits merchants from transferring the Merchant Discount Rate (MDR) burden to consumers. This study aims to examine the practice of additional fee imposition in QRIS transactions and analyze its legal framework under Indonesian law. The research applies a normative juridical method with statutory and conceptual approaches. The findings indicate that such additional charges constitute a violation of payment system regulations and may result in consumer disadvantage.